Entrepreneurial Potential of Students Graduating from Translation Studies - Klimkowska, Katarzyna; Klimkowski, Konrad (HERMES - Journal of Language and Communication in Business, 2020)
Entrepreneurship is becoming a central issue in social, economic and educational policies globally. It is classified among the key assets that a contemporary university graduate needs to successfully enter the labour market – as an employee or a freelancer. Academic students who specialize in translation care about how their education translates onto their career. In this article, the authors present results of the research on how a selection of 436 Polish students of full-time translation courses perceive their future professional functioning in a hard and a soft-skill perspectives. The diagnostic procedure developed in the article can be of use to translation curricula designers and teachers in getting to know what their students think about being entrepreneurial translators. The data presented also show where educational interventions can be in place. A list of suggested didactic activities to exemplify such interventions is also provided.